High-resolution dendrometer measurements reveal different responses of Douglas-fir to extreme drought in 2018 depending on soil and rooting characteristics - Spangenberg, Göran; Zimmermann, Reiner; Küppers, Manfred; Hein, Sebastian (Frontiers in Plant Science, 2024)
Introduction: Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) is considered an important nonnative substitute tree species in Europe, especially for Norway spruce (Picea abies (L.) Karst.), mainly due to its higher drought tolerance. However, Douglas-fir has also shown increasing mortality in certain regions of the world. One of the main reasons is the increase in drought periods due to climate change. There is still a need for research on the influence of important soil properties and rooting characteristics on the drought tolerance of Douglas-fir. Therefore, wWe aimed to analyzed the influence of soil texture, plant-available water capacity (PAWC), fine root density, and effective rooting depth on water status and thus drought stress in Douglas-fir during the extreme drought of 2018. Methods: We selected seven closely spaced sites along a soil texture gradient from sand to clay at an elevation of ca. 500 m a.s.l. in southern Germany and determined soil physical and rooting characteristics. Water status parameters and growth duration were derived from dendrometer data at five Douglas-firs per site. The influence of soil and rooting characteristics on these drought stress-related parameters was analyzed using mixed-effects models. The focus was on two summer drought periods in 2018. Results and discussion: In the initial stage of the extreme summer drought of 2018 (in June), a higher PAWC and a higher fine root density reduced drought stress. However, these influences were no longer noticeable in the later stage of drought (in August), probably due to deeper soil desiccation. In August, a higher effective rooting depth reduced drought stress. Soil texture had a significant influence, particularly on growth duration. This study provides information on site selection for Douglas-fir cultivation under the predicted increase in severe drought, showing the importance of deep and intensive rooting, and points to the need for combined above-and belowground investigations for a better understanding of the drought response patterns of tree species.